Dentifrícios fluoretados: estudos de interferentes na concentração e análise de flúor por potenciometria - Meira, Karla Maria Simões (2015)
Objective: The objectives of this study were: a) determine the concentration of fluoride ion (FI), total soluble fluoride (FST), and total fluoride (FT) in toothpaste containing sodium monofluorophosphate (MFP) that were commercialized in the state of Paraiba. It was sought to investigate whether the brand, place of sale (mesoregion) and storage (the presence air conditioning) could play a role in these concentrations. It was also aimed to analyze the influence of a natural compound in fluoride potentiometric reading on not traded experimental toothpastes. Materials and Methods: For Study 1, samples (n = 57) were collected in 14 cities drawn from 4 mesoregions. Analyses were performed in triplicate using specific electrode for fluoride. Data were analyzed using descriptive statistics and ANOVA. For Study 2, the analyzes of samples (n = 59) were carried out in 3 phases: 1) determine the concentration of fluorine FT, FST and FI by direct reading; 2) determine the concentration of FT HMDS (gold standard) 3) determine the concentration of TF in toothpaste containing MFP experimental model containing different concentrations of hydrocolloid and mucin. Results: In Study 1, it was found that all the analyzed dentifrices exhibited FT values below 1500 ppm regardless of their mesoregion and brand. The average concentrations of FST were low, ranging between 750-800 ppm. The average concentrations (DP) of FI per establishment with and without air conditioning were 281.14 (21.75) and 262.72 (69.01) respectively (p> 0.05). For the second study, we observed a decrease of the concentration of dentifrice FT evaluated by directly reading when compared with the HMDS (gold standard). At a concentration of 50% in the dentifrice formulation, the hydrocolloid proved to interfere with the direct analysis of the total fluorine (947.65 ppm) compared to a sample without the presence of the natural compound (1095,52ppm) .When analyzed by HMDS, these same samples showed concentrations (1812.44) and (1525.37) respectively. Conclusion: The fluoride concentrations in toothpastes do not exceed the maximum allowed legally, however, they proved to be below than the ideal concentrations (1000 ppm). The fluoride concentrations in toothpastes sold in Paraiba were not influenced by storage locations and regions of the state. The Hydrocolloid present in the toothpaste formulation for fluoride substantivity appears to interfere with the direct analysis by potentiometric once it compromises the fidelity of the results.